Le nouveau développementalisme : propositions et limites - Georges Flexor; Robson Dias da Silva; Jenifer Pinto (Cahiers des Amériques Latines, 2017)
This article aims to critically review the perspective of New Developmentism, that has gained ground in brazilian economic and social debate in recent years. In particular, it seeks to highlight the role of the regulation State. A critical review of the main authors with the New Developmentalism, shows that it is first and foremost a macroeconomic strategy to promote the re-industrialization of Brazil by way of manufactured exports. However, this macroeconomic strategy does not sufficiently take care of the importante political and even economic restrictions.